Inhibition of Isorhamnetin on β-Catenin/Tcf Signaling and β-Catenin-Activated Melanogenesis - Seyeon Park; Hana Choi; Yun Joo Kim (Journal of Basic & Applied Sciences, 2021)
Activated β-catenin/T-cell factor (Tcf) signaling plays various roles in human cell mechanisms. We identified the inhibitory effect of isorhamnetin against β-catenin/Tcf signaling in β-catenin activated cells. Isorhamnetin inhibited the transcriptional activity of β-catenin/Tcf in HEK293 cells transiently transfected with a constitutively active mutant β-catenin gene. Also, isorhamnetin inhibited theβ-catenin-activated melanogenesis in B16F1 cells. Regarding the inhibitory mechanism, the shift assay showed that the binding of Tcf complexes with its specific DNA-binding sites was suppressed byisorhamnetin. Western blot analysis showed a decreased level of β-catenin in nucleus caused by isorhamnetin. These results suggest that the isorhamnetin acts as a negative regulator of β-catenin/Tcf signaling and its inhibitory mechanism is related to the decreased binding of β-catenin/Tcf complexes to consensus DNA.